Sustainable, Extensible Documentation Generation Using inlinedocs - Toby Dylan Hocking; Thomas Wutzler; Keith Ponting; Philippe Grosjean (Journal of Statistical Software, 2013)
This article presents inlinedocs, an R package for generating documentation from comments. The concept of structured, interwoven code and documentation has existed for many years, but existing systems that implement this for the R programming language do not tightly integrate with R code, leading to several drawbacks. This article attempts to address these issues and presents 2 contributions for documentation generation for the R community. First, we propose a new syntax for inline documentation of R code within comments adjacent to the relevant code, which allows for highly readable and maintainable code and documentation. Second, we propose an extensible system for parsing these comments, which allows the syntax to be easily augmented.